Developing competency-based assessment at Vocational High School (VHS) in Bali - Dessy Seri Wahyuni (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2021)
This paper aims to resolve the difficulties of implementing competency-based assessment (CBA) in vocational high school while practicing in the workplace. This research was performed employing a qualitative exploratory descriptive (QED) method. The respondents are 109 participants from vocational teachers, industry experts, VHS students, and technical certification organizations. The implementation of CBA generates the competency standards of graduates in schools that meet the industry's competency needs. CBA is carried out by creating competency levels, college and workplace learning as students practice doing industrial work. This study's findings suggest aspects of CBA that provide a fair degree of application of the student's business work activities and present an approach to explaining training that is not limited to learning contexts.